The first Lahu (Muhsur) Christians: A community in Northern Thailand - Walker, Anthony R. R. (Acta Orientalia Vilnensia, 2010)
Universiti Brunei Darussalam Between 10 to 20 per cent of all the Tibeto-Burman-speaking Lahu people now subscribe to one or another version of the Christian religion. The largest proportion of present-day Lahu Christians inherited the genre of this Western religion propagated by American Baptist missionaries in the former Kengtung State of Burma (from 1901 to 1966), in Yunnan (from 1920 to 1949), and in North Thailand (from 1968 to 1990). For this reason, it is often thought that pioneer American Baptist among the Lahu, William Marcus Young (1861–1936), was the first to induct a representative of this people into the Christian faith. In fact this is not the case. The first Lahu Christians lived in North Thailand, baptised by long-time Chiang Mai-based American Presbyterian missionary, Daniel McGilvary. This was in 1891, thirteen years before Young’s first baptism of a Lahu in Kengtung, Burma, in October 1904. The paper addresses three questions. Why were Lahu living in upland North Thailand in the early 1890s? Why did one small Lahu community decide to embrace the Christian religion? Finally, why, in stark contrast to Baptist Christianity in the Lahu Mountains, did this fledgling Lahu Presbyterian community disappear, apparently without trace, sometime after 1920?